2017
DOI: 10.1177/1363461517708120
|View full text |Cite
|
Sign up to set email alerts
|

Culturally prescribed beliefs about mental illness among the Akan of Ghana

Abstract: Mental illness is a culturally laden phenomenon, and different cultures have unique ways of constructing mental illness. In this study, conceptions of mental illness were explored among 30 participants of Akan descent in Ghana through individual and group interviews. Participants demonstrated a wide range of knowledge on mental illness indicating that poor self-care, deficits in social functioning, and disordered behaviors are the cardinal features of mental illness. The data revealed that Akan cultural belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 45 publications
3
32
1
Order By: Relevance
“…In particular, consumers who perceived that mental illness is noninfectious and treatable were more likely to access mental health services. The positive attitudes and beliefs in the present study seem contrary to the negative attitudes exhibited by consumers of mental health services in previous studies in Ghana . The earlier evidence confirms that there is an increasing level of stigmatizing attitudes perpetuated against consumers of mental health services in Ghana.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In particular, consumers who perceived that mental illness is noninfectious and treatable were more likely to access mental health services. The positive attitudes and beliefs in the present study seem contrary to the negative attitudes exhibited by consumers of mental health services in previous studies in Ghana . The earlier evidence confirms that there is an increasing level of stigmatizing attitudes perpetuated against consumers of mental health services in Ghana.…”
Section: Discussioncontrasting
confidence: 70%
“…[3][4][5] The current evidence confirms that most consumers of Ghana. 18,20,21,45 The earlier evidence confirms that there is an increasing level of stigmatizing attitudes perpetuated against consumers of mental health services in Ghana. The negative attitudes mostly originate from the public, service providers, family caregivers, and consumers themselves.…”
Section: Attitudes and Beliefsmentioning
confidence: 73%
See 1 more Smart Citation
“…Yendork et al [ 31 ] reported that congregants of charismatic churches also attributed mental illness to supernatural and diabolical forces. However, Opare-Henaku and Utsey’s [ 32 ] exploration of indigenous Akan concepts of mental illness suggests that such notions are likely influenced by cultural perceptions of illness causation, further emphasizing the syncretic nature of the neo-prophetic churches.…”
Section: Discussionmentioning
confidence: 99%
“…The phrase is also used for mental illness. For this reason, people with psychotic symptoms, and even diagnoses of schizophrenia, seek out spiritual help as a pathway to healing (see, e.g., Opare‐Henaku & Utsey 2017; Read 2012).…”
Section: The Fante Lexicon For ‘Mind’mentioning
confidence: 99%